School Adjustment Problems and Coping Strategies of Senior High School Students of a Catholic School - Fillomena, Remelyn E.; Maravilla, Ma. Wilma M. (Philippine Social Science Journal, 2020)
School adjustment and coping strategies are vital elements of students’ lives because they help them adapt and function well to their environment, thereby preventing countless mental health problems. However, despite the robust information about the importance and benefits of adaptability or adjusting well to one’s environment, many students still encounter school adjustment problems. Luckily, students often resort to various coping strategies in order to deal with their problems effectively. Hence, the paper determined the degree of school adjustment problems and the extent of coping strategies of senior high school students of a Diocesan Catholic school in Antique during the School Year 2019-2020. Likewise, it determines the correlation between school adjustment problems and students’ coping strategies and whether good coping strategies predict school adjustment problems.